Filamin A (FLNA) mutation—A newcomer to the childhood interstitial lung disease (ChILD) classification - Susan C. Shelmerdine; Thomas Semple; Colin Wallis; Paul Aurora; Shahin Moledina; Michael T. Ashworth; Cátherine M. Owens (2017)
Interstitial lung disease (ILD) in infants represents a rare and heterogenous group of disorders, distinct from those occurring in adults. In recent years a new entity within this category is being recognized, namely filamin A (FLNA) mutation related lung disease. Our aims are to describe the clinical and radiological course of patients with this disease entity to aid clinicians in the prognostic counseling and management of similar patients they may encounter.A retrospective case note review was conducted of all patients treated at our institution (a specialist tertiary referral childrens' center) for genetically confirmed FLNA mutation related lung disease. The clinical presentation, evolution, management and radiological features were recorded and a medical literature review of Medline indexed articles was conducted.We present a case series of four patients with interstitial lung disease and genetically confirmed abnormalities within the FLNA gene. Their imaging findings all reveal a pattern of predominantly upper lobe overinflation, coarse pulmonary lobular septal thickening and diffuse patchy atelectasis. The clinical outcomes of our patients have been variable ranging from infant death, lobar resection and need for supplemental oxygen and bronchodilators.The progressive nature of the pulmonary aspect of this disorder and need for early aggressive supportive treatment make identification crucial to patient management and prognostic counseling.